Estilos de negociación de conflicto y satisfacción sexual en parejas adventistas de Lima Metropolitana - Quilla Varga, Roxana (2019)
Objective: Determine the relationship between conflict negotiation styles and sexual satisfaction. Materialsand Methods: The design is not experimental, Cross-sectional study and correlational style. The population isconstituted for person’s married Adventist denomination whom ages range between 24 and 75 years. The sampleof the population in studies was estimated using non-probability procedures amounting to 67 subjects. It used TheNegotiation Styles Inventory of Conflict and of Levinger and Pietromonaco which has 30 items and measures fourstyles; and the Sexual Satisfaction Inventory from Alvarez-Gayou, Honold and Millan, with 29 items, and classifiedinto three levels. Results: It has been found that the study variables are associated (F=4.793, p<0.05). The styleof conflict resolution collaboration and Avoidance has significant relationship with sexual satisfaction sexual (r =0.441, p < 0.01; r = 0.235, p <0.05); while the styles accommodation and competition are not associated with sexualsatisfaction (r = 0.055, p > 0.01; r = -0.032, p > 0.01). Conclusions: Both study variables have some relationshiSpecifically the collaborative style and avoidance is positively correlated with sexual satisfaction, as opposed toaccommodation and competition styles have no relation to sexual satisfaction.